Restorative Justice in the Handling of Criminal Acts Related to Information and Electronic Transactions - Pendi Wibison; Novi Indah Earlyanti (Faculty of Law, Universitas Pekalongan, 2026)
This study was motivated by the fact that investigators from the Cyber Crime Directorate of the Indonesian National Police often do not prolong the case process and encourage victims/reporters and perpetrators/reported parties to resolve the case through deliberation. This is based on Indonesian National Police Regulation No. 8 of 2021 concerning the Handling of Criminal Acts based on restorative justice. The purpose of this study is to objectively determine the handling of ITE criminal cases using a restorative justice approach, the effectiveness of the resolution, and the factors that influence it. The theoretical basis uses the Legal System, Theory of Justice, Theory of Legal Limiting Principles, Concepts of Investigation and Inquiry, Concept of Democting Policing, Concept of Restorative Justice, Concept of ITE Crimes, and Concept of Police Science. A qualitative approach was used with a case study method, with primary and secondary data sources using interview, observation, and document study techniques. Data analysis techniques included data reduction, data presentation, and conclusions. The results of the study show that 1) The handling of ITE criminal cases with a justice-based approach at the Cyber Crime Directorate of the Indonesian National Police is guided by Perpol Number 8 of 2021 concerning the Handling of Criminal Acts Based on Restorative Justice, ST Kapolri No. 339/II/Res. 1.1.1/2021 concerning Guidelines for Handling Criminal Cases and SE Kapolri Number SE/2/11/2021 concerning Ethical Cultural Awareness to Create a Clean, Healthy, and Productive Indonesian Digital Space. Investigators adhere to the principle that criminal law is a last resort in law enforcement (ultimatum remedium) and prioritize restorative justice; 2) The settlement of ITE criminal cases using a restorative justice approach has not been effective, even though there is a clear legal framework, but its implementation has not yet led to the optimal application of the philosophy of restorative law enforcement; 3) Factors that influence the effectiveness of handling ITE criminal cases with a restorative justice approach include legal substance, legal structure, and legal culture.